3D printers : a beginner's guide - Bothmann, Oliver, frey50 (East Petersburg, PA Fox Chapel Publishing, 2015)
"Provides a detailed explanation of the basics of purchasing and using 3D printers for total beginners."--
Includes bibliographical references and index
Keywords: Three-dimensional printing